Bernard Lewis dan Apologia Barat - Adian Husaini (Universitas Darussalam Gontor, 2017)
Bernard Lewis was known as a good writer and an orientalist who concentrated on Islamic and Jewish history. Exactly, he was the one who introduced the discourse of ‘Clash of Civilizations’ for the first time through his article “The Roots of Muslim Rage” in Atlantic Monthly journal released on September, 1990. It was written as a preparation to decide a “new enemy” of the West after the Cold War. Lewis called Western Civilization by “Christian Civilization”, which mean that its root was Christian religion. According to Lewis, the conflict between Islam and the West (Christian) had been starting since hundred years ago and it is increasing. He noted, since the rise of Islam, there was physical contact between Islam and Christian happened when the Prophet Mohammed Saw began his mission in the early 7th century. During that era, the whole region of Mediterranean which was a part of Christendom had switched to be Islamic zone. Lewis was so close to the White House authority and it caused his views containing political thought which guided the United States of America to decide their foreign policy. Therefore, he lost his objectivity as a scientist to reveal some facts along relationship between Islam and the West. It is obviously explained in his book “The Crisis of Islam: Holy War and Unholy Terror”. The book is such an apology of the West for their foreign policy implementation, especially toward Islamic world. This article reveals how Lewis defended political policy of Western countries, especially USA.